Changing Places: Las Vegas/San Francisco/New Orleans - Kolster, Michael (Consilience, 2010)
Dates: 2001-2007Locations: Las Vegas/San Francisco/New OrleansSupporting Institution: funding for the project has been provided by Bowdoin College These photographs come from a long-term and ongoing project concerned with how we perceive and are affected by changes in the places we inhabit. New Orleans finds itself in a precarious position relative to the “natural” demands of its geographic location. Eighty percent of the city was flooded in 2005; as many of us now realize, most of the city is located below the level of the water that borders it. Due to where it is physically located, in 50 years New Orleans will most likely look nothing like it does today.Coincident to or perhaps because of its location, New Orleans has developed an identity that represents a diversion from the cultural norms associated with mainstream America. Known as the Big Easy for the ease with which musicians could find work, it displays front and center its difference from the rest of America during its celebration of Mardi Gras.What should be an obvious truth, that a place’s physical location and features have a profound affect on the lives and outlooks of its inhabitants, is often overlooked. Saying we live “in” a place, rather than “on” or “with” it, concedes how entirely a place encompasses us physically. It acknowledges the pervasive affect the place’s external imperatives have upon our psyches, our perceptions of self and others, andthe desires we pursue.Now that popular consensus is embracing the fact that our world is growing warmer, the uncertain futures this city faces today may well be a harbinger of change facing the places we all live in. Has a sequence of events already been set in motion that will irrevocably alter how and where all of us will be able to live? And if so, how will this fact affect how we relate to each other and to the places we inhabit?These photographs describe relationships between elements in the landscape that are specific to a particular day, hour, and fraction of a second. What is important to keep in mind is that each triptych presented here comprises a series of individual and distinct photographs. Each individual “frame” within the triptych is its own point in time and each corresponds to a distinct piece of film that I exposed. Taking in the scene presented by the triptych is analogous to how each of us encounters a prospect. By pausing slightly and regularly we set into motion a mental “imagining” in order to see things more completely.I hope each piece’s particularity, its reference to a specific location in time as well as space, stimulates speculation about how different that place appears at this very moment, were you able to behold it for yourself. And more exciting is to ponder what it might look like tomorrow, next month, and 50 years hence.